Diagnostic Performance of Western Blot for Congenital Toxoplasmosis: A Systematic Review and Meta-Analysis - Serna R, Sebastián; Restrepo-Duque, Maria Antonia; Arredondo-Torres, Jocelyn A; Fandiño-Lopez, Juan D; Mosquera-Solano, Luis F; Gomez-Marin, Jorge E (International Journal of Medical Students, 2025)
Background: Congenital toxoplasmosis results from infection with the parasite Toxoplasma gondii, which is transmitted from mother to child during pregnancy. Although Western blot is considered the most sensitive diagnostic tool for congenital toxoplasmosis, its diagnostic performance has not been subjected to meta-analysis. Methods: We conducted a systematic review and meta-analysis by performing literature searches across PubMed, Scopus, and Web of Science. The search strategy included the terms "western blot OR immunoblot" AND "congenital toxoplasmosis." The selected studies were required to meet specific inclusion criteria, which involved comparing the performance of the western blot test against the gold standard criteria for permanence of IgG after 10 months of age. These studies had to be case and control studies. The data obtained from the studies were then organized into an evidence synthesis table and the sensitivity, specificity, and Diagnostic Odds Ratio (DOR) index were calculated. This meta-analysis was performed in compliance with the recommendations of PRISMA guidelines. Results: After evaluating the selection criteria, we identified 44 articles; however, only 10 were selected for the meta-analysis. Western blot assay demonstrated a pooled sensitivity of 93.8% (95% CI: 79.2-98.4) and a pooled specificity of 96.6% (95% CI: 89.8-98.9) for the diagnosis of congenital toxoplasmosis. Six of the 10 studies had a DOR higher than 300, whereas the in-house method yielded a lower DOR of 1.2. Conclusions: This meta-analysis confirmed the utility of well-standardized western blot tests as a dependable diagnostic approach for congenital toxoplasmosis in terms of both sensitivity and specificity.